Aberrant fucosylation of glycosphingolipids in human hepatocellular carcinoma tissues. Issue 1 (31st July 2013) - Zhu, Jian; Wang, Yanping; Yu, Yunhui; Wang, Zheng; Zhu, Tingting; Xu, Xiukun; Liu, Haiyan; Hawke, David; Zhou, Dapeng; Li, Yunsen
Abstract Backgrounds & Aims Glycosylation promoting or inhibiting tumour cell invasion and metastasis is of crucial importance in current cancer research. Tumour‐associated carbohydrate antigens are predominantly expressed on the tumour cell surface. Glycosphingolipids (GSLs) are members of the family. To perform glycosphingolipidomic assays on neutral GSLs obtained from solid hepatocellular carcinoma (HCC) tissues and paired peritumoural tissues by linear ion trap quadrupole‐electrospray ionization mass spectrometry. Methods Qualitative and quantitative analysis of fucosylated neutral GSLs was performed in the positive ion mode on the LTQ‐XL mass spectrometer and MALDI‐TOF‐MS. Results A group of fucosylated neutral GSLs in HCC was found to be expressed higher in the tumour tissues, as their proportion in total cellular GSLs was 3.3‐fold higher in the tumour tissues than in the peritumoural tissues (P < 0.01). Moreover, qualitative analysis of the aberrant fucosylated GSLs were completed, and seven types of fucosylated GSLs that contained terminal Fuca2Gal‐ structure were identified by mass spectrometry. Conclusions Our results may lead to improved immunotherapy of HCC and contribute to understanding the role of aberrant fucosylated GSLs in the development and progress of HCC in following studies.